A Novel Test Method to Determine the Wear Resistance of Agricultural Cutting Tools with an Analyzing Method Based on an Ellipse-Fit Algorithm. (5th May 2015) - Jahr, Andreas; Bongartz, Robert; Sim, Hunn; Pillmann, Alex
Abstract : Cutting belongs to the essential techniques in many fields of application in agricultural engineering. Cutting tools in agriculture are exposed to a high amount of abrasive wear and impact stress. Increasing the wear resistance of cuttings tools has a high significance for the efficiency and profitability of agricultural machinery. Blunt and deformed blades decrease the energy efficiency and the cutting quality. Blade failures cause machine breakdowns and increase labor and material costs. To enable a consistent and systematic optimization of the blades, a suitable testing method is necessary. Conventional field tests do not provide comparable and repeatable results. Therefore, a test method developed at the FMDauto in cooperation with the Ennepetaler Schneid- und Mähtechnik (ESM) GmbH & Co. KG is presented. The test bench provides standardized and repeatable conditions with a similar wear pattern which is found during field operations. One of the remaining challenges is a clear wear characterization. Existing analyzing methods do not consider the energy efficiency and do not determine the edge holding property clearly. In this paper, a new analyzing method based on an ellipse-fit method is introduced to rate the geometrical shape of the cutting edge and examine the wear resistance of different blades.